Electoral cycles, partisan effects and U.S. immigration policies - Marcus Drometer; Romuald Méango (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Using a panel of naturalizations in U.S. states from 1986 to 2012, we empirically analyze the impact of elections on immigration policy. Our results indicate that immigration policy is (partly) driven by national elections: there are more naturalizations in presidential election years and during the terms of Democratic incumbents. Further, the partisan effects are more pronounced in politically contested states.
Keywords: H11; D72; F22; 330